2004
DOI: 10.1016/j.jmpt.2004.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal Muscles and Intervertebral Dysfunction: Part One

Abstract: Although little direct evidence exists of the nature of clinically detected paraspinal tissue texture change, the concept of reactive muscle contraction appears plausible. Increased paraspinal EMG activity associated with LBP does not appear to be mediated by a simple protective reflex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 40 publications
1
41
1
2
Order By: Relevance
“…J Orthop Sports Phys Ther 2015;45 (9) 21 Changed coordination between paraspinal muscles appears to be consistent with clinical observations of reduced ability to move the lumbar spine independently of the thorax (ie, poor "dissociation" of lumbar and thoracolumbar motion) in some individuals. 3,25 Although poorly dissociated spinal movement may be relevant to LBP, clinical methods to assess this function require validation.…”
Section: T T Conclusionsupporting
confidence: 68%
See 1 more Smart Citation
“…J Orthop Sports Phys Ther 2015;45 (9) 21 Changed coordination between paraspinal muscles appears to be consistent with clinical observations of reduced ability to move the lumbar spine independently of the thorax (ie, poor "dissociation" of lumbar and thoracolumbar motion) in some individuals. 3,25 Although poorly dissociated spinal movement may be relevant to LBP, clinical methods to assess this function require validation.…”
Section: T T Conclusionsupporting
confidence: 68%
“…Intertester reliability has are able to change their motor behavior, the increment in the total score of the LBP group was approximately half that achieved by the pain-free group. As the training involved specific cognitive attention to movement and muscle activity (ie, cognitive skill training), the difference could be a consequence of deficits in proprioception 14 or muscle function, 1,5,9,19 or may indicate a change in the ability of the group to learn a new task. 26 Individuals with LBP may require longer and/or more intense training.…”
Section: Relevance For Identification Of Lbp Subgroupsmentioning
confidence: 99%
“…23,24 Such spasms are thought to act as a protective mechanism, splinting injured areas of the spine. Injuries may be superficial such as strain/sprain or more serious such as disk protrusion, spondylosis, or fracture.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review has shown that the concept of reactive muscle contraction associated with intervertebral dysfunction seems plausible (Fryer et al, 2004a). The deep paraspinal muscle inhibition observed during dynamic and static activities was used as a theoretical framework for a possible relationship between dysfunctional muscle activity and tissue texture change findings with SD.…”
Section: Physiological Studiesmentioning
confidence: 99%